Hypercoagulability and High Lipoprotein(a) Levels in Patients with Central Retinal Vein Occlusion - Bandello, Francesco; Vigano’ D’Angelo, Silvana; Parlavecchia, Mariella; Tavola, Alessandra; Della Valle, Patrizia; Brancato, Rosario; D’Angelo, Armando (Thrombosis and Haemostasis, 1994)
A series of coagulation parameters and lipoprotein(a) (Lp(a)) were explored in plasma from 40 patients with central retinal vein occlusion (CRVO, non-ischemic type n = 12; ischemic type n = 28) free of local and systemic predisposing factors, 1 to 12 months after the acute event. Forty age- and sex-matched patients with cataract served as controls. Prothrombin fragment 1.2 (FI.2), D-dimer, FVII:C - but not FVII: Ag - were higher and fibrinogen was lower in CRVO patients than in controls. Patients with non-ischemic CRVO had higher FI .2 and FVII:C and lower heparin cofactor II than patients with ischemic CRVO. Lp(a) levels greater than 300 mg/1 were observed in 12 patients with CRVO and in 4 controls (30% vs 10%, p <0.025). Patients with high Lp(a) - consistently associated with the S2 phenotype - had higher FVII:C, FVII:C/Ag ratio, and fibrinogen than the remaining CRVO patients. Plasma FI.2 and D-dimer correlated fairly in controls (r = 0.41) and patients with normal Lp(a) levels (r = 0.55), but they did not in the group of patients with high Lp(a) (r = 0.19), where the latter parameter was negatively related to D-dimer (r = −0.55). There was no dependence of the abnormalities observed on the time elapsed from vein occlusion. The findings of activated FVII and high FI.2, D-dimer, and Lp(a) are not uncommon in patients with CRVO. Increased thrombin formation with fibrin deposition and impaired fibrinolysis may play a role in the pathophysiology of CRVO and require specific treatment